2022
DOI: 10.1049/stg2.12072
|View full text |Cite
|
Sign up to set email alerts
|

A DFT‐based method for estimating interharmonics in wind power generation

Abstract: This paper introduces a discrete Fourier transform (DFT)-based method for estimating the amplitudes and frequencies of interharmonics, which arise from the interaction between wind power generators and electric power systems. This method exploits the synergy of choosing signal enhancement, mains frequency estimation, and re-sampling techniques. Consequently, it accomplishes a cost-effective estimation process. The performance results show that signal enhancement and re-sampling techniques are necessary to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Interharmonics mainly originate from nonperiodic changes in current and voltage caused by loads operating in nonsteady states and/or amplitude modulation in control strategies [4]. Several factors contribute to their generation, including the use of nonlinear loads, double conversion systems, cascaded subsynchronous converters [5,6], asymmetric induction motors and the incorporation of AC/DC and DC/AC conversions in renewable energy sources such as photovoltaic systems [7][8][9] and wind turbines [10,11]. Additionally, double-stage systems, which consist of two AC systems operating at different frequencies interconnected through a DC link [12,13], have also been identified as significant sources of interharmonics.…”
Section: Introductionmentioning
confidence: 99%
“…Interharmonics mainly originate from nonperiodic changes in current and voltage caused by loads operating in nonsteady states and/or amplitude modulation in control strategies [4]. Several factors contribute to their generation, including the use of nonlinear loads, double conversion systems, cascaded subsynchronous converters [5,6], asymmetric induction motors and the incorporation of AC/DC and DC/AC conversions in renewable energy sources such as photovoltaic systems [7][8][9] and wind turbines [10,11]. Additionally, double-stage systems, which consist of two AC systems operating at different frequencies interconnected through a DC link [12,13], have also been identified as significant sources of interharmonics.…”
Section: Introductionmentioning
confidence: 99%
“…In [32], it was shown that the combination of a re-sampling method, based on the Lagrange function, with the IpDFT is an interesting strategy to estimate the harmonics and interharmonics components for frequency deviation scenarios and noisy signals. Although this method presents accurate results, the analysis is made until the second harmonic and the re-sampling method was based on the Lagrange function.…”
Section: Introductionmentioning
confidence: 99%